DIABLOCK: PROTOTIPE REKAM KESEHATAN PERSONAL BERBASIS MOBILE BAGI DIABETESI - Nurvita Wikansari; Dian Budi Santoso (Jurnal Informasi Kesehatan Indonesia (JIKI), 2022)
BPJS Kesehatan, as an institution that manages national health insurance in Indonesia, has launched a chronic disease management program where one of the diseases that is specifically monitored is Diabetes Mellitus. Health data is limited to those collected from health service facilities. On the other hand, patients have not been involved to participate in managing this health data. A personal health record specifically for diabetics is needed that can fulfill the data collection aspect by actively involving patients. This study aims to develop a personal health record prototype specifically according to the needs of diabetics. Subjects and Method: This study used a participatory action research design involving 7 people with diabetes as subjects as well as research participants. Data collection for needs analysis was carried out through online FGDs, the results then used as the basis for developing a prototype by involving research subjects to provide input until the prototype was developed. Results: A prototype of a personal health record for diabetics has been created named “DiaBlock” which was developed on an Android-based mobile platform. “DiaBlock” has 7 main features, namely consultation, medical record, glucolator (blood sugar calculator), screening, sugar chart, reward, and health tips. Conclusion: “DiaBlock” has been developed according to the needs of diabetics. Various features such as health articles, record of independent blood sugar measurements, and rewards are expected to motivate diabetics to be able to control and implement a healthy lifestyle.